The Strategy of PAI Teachers in Improving Students' Morals Through TPQ Extracurricular Activities - Wahidiyanti, Nur Amaliyah; Abdulloh (Global Action and Education for Society, 2025)
This study focuses on three main issues: the moral condition of students, the teaching strategies used by Islamic Education (PAI) teachers to improve students' morals, and moral indicators. The aim of this research is to explore, analyze, and describe the moral condition of students, moral indicators, and the approaches used by PAI teachers to enhance students' morals at SMP Wahidiyah Kepanjen Malang. This research employs a qualitative approach with data collection methods including observation, interviews, and documentation, involving Islamic Education teachers, the principal, and students as respondents. The results of the study indicate that the strategies employed by PAI teachers at SMP Wahidiyah Kepanjen successfully enhance students' morals through TPQ extracurricular activities, utilizing cognitive tests in the form of student monitoring books. As a result, SMP Wahidiyah is able to produce students who possess knowledge of the Qur'an and can integrate its values into their daily lives.